2016
DOI: 10.5430/jnep.v6n10p122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the psychometric properties of the nursing students’ attitudes toward mental health nursing and consumers instrument

Abstract: The present study aimed to evaluate the psychometric properties of the instrument "Nursing Students' Attitudes Toward Mental Health Nursing and Consumers" for use among nursing students in Brazil. The subjects were 91.3% female and 8.7% male and their ages ranged from 18 to 58 years, with a mean (M) of 21.9 years and a standard deviation (sd) of 3.88 years. The study included students from the undergraduate course in nursing of five higher public education institutions, with a total of 393 students. Of these, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The initial criterion of communalities <0.400 was established for deleting the item from the instrument, a minimum of 0.6 for the Kaiser-Meyer-Olkin index (KMO) for the sample to be deemed adequate and p<0.010 for Bartlett's test of sphericity. (Soares & Luís, 2016). The Bartlett's test of Sphericity (Bartlett, 1950) achieved statistical significance value with p<0.500 (Hair et al, 1998;Tabachnick & Fidell, 2013) and indicated that the items used in the analysis were suitable.…”
Section: Factor Analysismentioning
confidence: 99%
“…The initial criterion of communalities <0.400 was established for deleting the item from the instrument, a minimum of 0.6 for the Kaiser-Meyer-Olkin index (KMO) for the sample to be deemed adequate and p<0.010 for Bartlett's test of sphericity. (Soares & Luís, 2016). The Bartlett's test of Sphericity (Bartlett, 1950) achieved statistical significance value with p<0.500 (Hair et al, 1998;Tabachnick & Fidell, 2013) and indicated that the items used in the analysis were suitable.…”
Section: Factor Analysismentioning
confidence: 99%